Penguatan Gender dalam Pengambilan Keputusan Birokrasi di Kabupaten Bone Bolango - Hunawa, Robby (Universitas Gorontalo, 2018)
The long-term goal of this research is the birth of the process of drawing womens involvement in the bureaucratic decision-making process, and the gender reinforcement model in bureaucratic decision making in Bone Bolango District. The target of the research will be done by stages: 1) identify the problem of constraints faced; and 2) to formulate a model of gender reinforcement in bureaucratic decision making. The research method used is qualitative research with data collection techniques through: interview, documentation, and FGD. Further data collected will be analyzed data triangulation. The result of the research is the birth of a model of gender reinforcement in decision making bureaucracy. The impact of the study will provide answers on womens partisifasi in decision making. During this time the existence of women is very much ruled out. The presence of female figures in the public dimension brings new trends in the context of government. Women want to be treated proportionally. This tendency has implications for the inclusion of women to compete with men to become leaders.